2012
DOI: 10.1136/sextrans-2012-050601c.8
|View full text |Cite
|
Sign up to set email alerts
|

P8 Tests of recent HIV infection in clinical practice: the patient perspective

Abstract: Aims/Objectives To promote the importance of HIV testing, and to see if the outreach was successful in targeting a less tested population of MSM. Methods The promotion was determined by the "opportunities to view" key messages. Individuals tested in the bar completed a form collecting age, gender, orientation, time since last HIV test, unprotected anal (UAI) or vaginal sex. Similar information was collected from 100 patients walking into the generic service for an HIV test on the same day. Age groups <25, 26e3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Two recent studies found that patients valued information about the likely timing of their infection, and no negative outcomes were experienced by those receiving these results [74] [75]. Another study indicated that clinicians found the results helpful and were comfortable discussing these with patients, particularly in the context of possible HIV seroconversion illness [76].…”
Section: Returning Results To the Patientmentioning
confidence: 99%
“…Two recent studies found that patients valued information about the likely timing of their infection, and no negative outcomes were experienced by those receiving these results [74] [75]. Another study indicated that clinicians found the results helpful and were comfortable discussing these with patients, particularly in the context of possible HIV seroconversion illness [76].…”
Section: Returning Results To the Patientmentioning
confidence: 99%